2006
DOI: 10.1007/s11606-006-0258-x
|View full text |Cite
|
Sign up to set email alerts
|

Brief report: Methadone treatment of injecting opioid users for prevention of HIV infection

Abstract: OBJECTIVE:To assess the effects of oral substitution treatment for opioid-dependent injecting drug users on HIV risk behaviors and infections.DATA SOURCES: Multiple electronic databases were searched. Reference lists of retrieved articles were checked. METHODS:Because of varying methodologies of available studies, this systematic review was limited to a descriptive summary, looking at consistency of outcomes across studies. RESULTS:Twenty-eight studies involving methadone treatment were included in the review.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 26 publications
3
40
0
2
Order By: Relevance
“…2,3 The present study found a significantly greater reduction in drug injection from baseline to follow-up for the IM condition compared to the WL condition. Despite this finding, the condition×time interaction for the overall ARA drug use behavior score was nonsignificant, perhaps because 60.2% of the study sample was non-injectors and the injectors reported low levels of risky injection practices at baseline.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…2,3 The present study found a significantly greater reduction in drug injection from baseline to follow-up for the IM condition compared to the WL condition. Despite this finding, the condition×time interaction for the overall ARA drug use behavior score was nonsignificant, perhaps because 60.2% of the study sample was non-injectors and the injectors reported low levels of risky injection practices at baseline.…”
Section: Discussionsupporting
confidence: 44%
“…1 There are limited data from RCTs of standard methadone treatment which incorporated an HIV risk measure 2,3 and even less from trials of methadone alone.…”
Section: Introductionmentioning
confidence: 99%
“…24 Effectiveness of opioid substitution treatment The best evidence of the effectiveness of drug dependence treatment in preventing HIV transmission among IDUs is for opioid substitution treatment programs using methadone and buprenorphine. [25][26][27] The evidence is much stronger for methadone than for buprenorphine treatment. 27,28 Methadone substantially reduces drug injecting and thereby the sharing of injecting equipment.…”
Section: Effectiveness Of Needle and Syringe Programsmentioning
confidence: 99%
“…[25][26][27] The evidence is much stronger for methadone than for buprenorphine treatment. 27,28 Methadone substantially reduces drug injecting and thereby the sharing of injecting equipment. 26,29 Seroprevalence studies suggest that reductions in injecting risk behaviour can result in reductions in HIV infection but relatively few (expensive and difficult) seroincidence studies have been published.…”
Section: Effectiveness Of Needle and Syringe Programsmentioning
confidence: 99%
“…17 Compared to abstinence-based treatment, OAT has been associated with increased retention in addiction treatment and employment, and reductions in incarceration, human immunodeficiency virus transmission, illicit drug use, opioid-overdose events, and mortality. [26][27][28][29][30][31][32] An alternative to OAT is naltrexone, an opioid antagonist. Naltrexone for OUD is administered as a monthly depot injection that prevents the user from experiencing opioid intoxication or dependence, and is associated with sustained abstinence.…”
Section: Medication-assisted Treatmentmentioning
confidence: 99%